Prehabilitation-plus for patients undergoing major lower limb amputation may reduce acute hospital and total hospital length of stay: a retrospective, matched, case-controlled pilot service evaluation. (2nd March 2022) - Fulton, Shelley; Baird, Tyson; Naik, Siang; Stiller, Kathy
Abstract : Background/Aims: 'Prehabilitation' refers to interventions that seek to enhance a person's functional capacity to help withstand a forthcoming stressor, such as major surgery. There is little research evaluating prehabilitation before major lower limb amputation. This study evaluated if a comprehensive multidisciplinary pre-admission programme, which included prehabilitation plus other interventions (eg education, home assessment and modifications), hereinafter called 'prehabilitation-plus', might shorten hospital length of stay by allowing earlier discharge home from hospital after major lower limb amputation. The aim of this study was to investigate the effect of prehabilitation-plus on hospital length of stay and discharge destination for patients undergoing major lower limb amputation. Methods: Seven patients receiving prehabilitation-plus were retrospectively matched with seven control patients in this case-controlled pilot service evaluation. Prehabilitation-plus was provided by a multidisciplinary team. Hospital length of stay was compared using Mann–Whitney U tests and discharge destination using Fisher's exact test. Results: Acute hospital and total hospital length of stay were significantly lower in the prehabilitation-plus group than the control group ( P =0.038 and 0.011 respectively). No significant difference was seen for rehabilitation hospital length of stay ( P =0.400). More prehabilitation-plus patients were discharged directly home after their acute hospital stay, but this was not significant ( P =0.286). Conclusions: Patients who received prehabilitation-plus had reduced acute hospital and total hospital length of stay compared to matched control patients. While these preliminary results are promising for the ability of programmes such as prehabilitation-plus to reduce hospital length of stay, further studies with more robust designs are required to confirm and extend this finding.